THE EFFECT OF OSTENSIVE APPROACH ON IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT, A CASE OF SMPN 10 KENDAR - Verliyani, Yesti (Journal of Teaching of English, 2019)
The background of conducting this research is the need to find out a method of teaching vocabulary that can be integrated into the four main skills, while focused still on students’ vocabulary. The objective of the research is to find out whether there is a significant effect of  ostensive approach on students’ vocabulary at the first grade of SMP Negeri 10 Kendari. This research is focused on the effect of ostensive approach based on students’ vocabulary achievement. The  design  of  the  study  was  Quasi experimental  design  which  two  group  in  given pretest and posttest. The instrument of this study was vocabulary test that consisted of 40 numbers and multiple- choice test consists of 20 items and there are 20 items of matching test. The population of this study  was all  the first  grade  students’  of  SMP  Negeri 10 Kendari  who  were registered in academic year 2015/2016 with the total number of students is 223. The researcher chooses class VII5 as experimental class  and  VII6  as control class and both of class consist of 30  students.  The researcher collected the data by giving pretest in two classes to know students’ prior knowledge, giving treatment which the researcher conducted teaching and learning process by using  ostensive approach in experimental class and using traditional approach in control class, then giving posttest to know the differences effect of the two approach toward the improving of students’ vocabulary achievement after treatment. The data collected analyzed by using SPSS 16 for windows in form independent-sample t test and the result of the analysis shows that there were significant differences between students who taught by ostensive approach and students who taught by traditional approach. Its’ proved by the result, the hypothesis testing show the value of probability (sig. 2 tailed) 0.004 lower than alpha value (0.05). It means that Ho was rejected and H1  totally accepted. Therefore, mean score experiment class was higher than control class (79.5000 > 69.4667). The mean score of experiment class was included in high criteria whereas the mean score of control class was included in moderate criteria.  It can be concluded that there is a significant effect of using ostensive approach on improving students’ vocabulary achievement at the first grade of SMPN 10 Kendari.  Keywords: Ostensive Approach, effect, vocabulary achievement.